Modeling of cutting of multilayer materials - Guts, Viktor; Gubenia, Oleksii; Lukianenko, Bogdan (My University, 2013)
In the food industry products which have homogeneous or difficult multilayer structure are cut. Process of cutting for each case has many differences. It is necessary to fix features of movement of a knife in different products behind structure, and to improve regime parameters of operation of the cutting equipment.Materials and methods. Mathematical simulation of movement of a knife in a product on the basis of the power assaying and the decision of differential second-kind equations is spent. For experimental researches installation of pendulum type with a knife that allows to change easily rate of a knife and a store of its kinetic energy is used. Mathematical sample pieces of cutting which allow to define force of cutting at different rates of a knife and product structure, and techniques of definition of factors, in mathematical sample pieces of cutting for different conditions of process are developed. If the product has a thin strong envelope, the force of cutting at knife approach to an envelope grows. It is reduced recommendations concerning conditions of movement of the cutting instrument, its orientation, concerning stratums to a product. At first it is necessary to cut a thin strong stratum, and then all volume of a product. It considerably reduces energy consumptions at cutting.
Keywords: cutting; food; regime; modellind; multilayer materials; різання; харчування; режим; моделювання; багатошарові матеріали; кафедра машин і апаратів харчових та фармацевтичних виробництв; кафедра екології та екоменеджменту